Prevalencia y factores de riesgo de la conducta suicida en adolescentes - Armijos Rosillo, María del Carmen (2023)
Suicidal behavior is a universal, social and timeless phenomenon that has generated great interest in the scientific community due to its high prevalence in adolescents and its potential impact on physical and psychological health. In recent years, the presence of risk factors has been shown to play a major role in the development and maintenance of suicidal behaviors. In view of this situation, the present research aims to describe the scientific evidence of suicidal behavior in adolescents in the American continent the last ten years, seeking to establish the prevalence and the most predominant risk factors associated with its development. A bibliographic review with descriptive and cross-sectional design was conducted, which included a search of scientific articles in the databases Dialnet, Scielo, Redalyc, Pubmed and Google Scholar during the period 2013-2023, based on inclusion and exclusion criteria, 20 scientific articles were selected as a representative sample of the researching work. The results obtained through scientific evidence indicated that suicidal behavior is highly prevalent in adolescents in the American continent, with suicidal ideation and attempts being the most frequent categories. Among the associated risk factors, we find psychological, social and family factors, with depression, anxiety, alcohol and tobacco consumption, chaotic family relationships and family dysfunctionality standing out as the main factors linked to the appearance and increase of suicidal behavior in adolescents. In conclusion, suicidal behavior has become a challenge for the health and scientific field due to the accelerated growth of its statistical figures, mainly in vulnerable groups such as adolescents, a fact that has been cataloged as the reference point for prevention and intervention in this problem